2021
DOI: 10.3389/fmed.2021.637875
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Prediction Model for Non-curative Resection of Early Gastric Cancer With Endoscopic Resection and the Evaluation

Abstract: Background and Study Aim: EGC, also known as Early Gastric Cancer is known to lack the lymph node metastasis and confined along the mucosa, which is treated through an endoscopic resection procedure that includes ESD (Endoscopic Submucosal dissection) and EMR (Endoscopic Mucosal Resection). However, some cases underwent residual disease, recurrence, or additional gastrectomy because of non-curative resection. The following research aims to delineate the threat factors causing the non-curative resection as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…It should be noted that endoscopy alone (even without CE) has almost 80 % accuracy in determining curability by ER, with several prediction models described to decide between ESD or surgery, with good results published in the literature [57][58][59]. Moreover, ESD does not preclude the possibility of subsequent surgery and should be seen as the most definitive T-staging modality.…”
Section: Stomach Lesionsmentioning
confidence: 99%
“…It should be noted that endoscopy alone (even without CE) has almost 80 % accuracy in determining curability by ER, with several prediction models described to decide between ESD or surgery, with good results published in the literature [57][58][59]. Moreover, ESD does not preclude the possibility of subsequent surgery and should be seen as the most definitive T-staging modality.…”
Section: Stomach Lesionsmentioning
confidence: 99%
“…In summary, we believe Our model contained three important factors: tumour size, tumour grade and depth of tumour invasion. In previous reports, tumour diameter affected lymph node metastasis in early gastric cancer, and the larger was the tumour diameter, the higher was the risk of LNM in patients (31). This phenomenon may be due to larger tumour diameters invading the surrounding tissues more easily.…”
Section: Discussionmentioning
confidence: 80%
“…65,73 Some authors have proposed prediction models for noncurative resection of EGC. 74,75 Kim et al 74 analyzed 1639 patients who had undergone ESD for EGCs and 272 were identified as being noncuratively treated with ESD. A large tumor size (≄20 mm), tumor location in the upper body of the stomach, the presence of ulcer, fusion of gastric folds, the absence of mucosal nodularity, spontaneous bleeding, and undifferentiated tumor histology were associated with noncurative resection of ESD.…”
Section: How To Decrease Adverse Events?mentioning
confidence: 99%
“…Risk scores should be used to estimate the probability of noncurative resection, and this data can be shared with patients to help them make more informed decisions 65,73 . Some authors have proposed prediction models for noncurative resection of EGC 74,75 . Kim et al 74 analyzed 1639 patients who had undergone ESD for EGCs and 272 were identified as being noncuratively treated with ESD.…”
Section: How To Improve Patient Selection?mentioning
confidence: 99%